1996
DOI: 10.1021/ie950445+
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Comparative Study of Energy-Integrated Distillation Schemes

Abstract: This paper presents results of a rigorous study and comparison of conventional and energy-integrated distillation schemes for the separation of ternary mixtures. The major part of this work is devoted to the design and simulation of the fully thermally coupled distillation column (Petlyuk or Kaibel column) with particular emphasis on the question of the fractional recovery of the middle component in the prefractionator and as a consequence the internal recycle streams. A comparative economic parametric study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 15 publications
0
72
0
Order By: Relevance
“…1c)). Theoretical studies [5][6][7] have shown that distillation schemes with side columns typically have energy savings of 30 % over conventional schemes.…”
Section: Introductionmentioning
confidence: 99%
“…1c)). Theoretical studies [5][6][7] have shown that distillation schemes with side columns typically have energy savings of 30 % over conventional schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the schemes that have received special attention are the systems with side columns: the thermally coupled system with a side rectifier (TCDS-SR, Figure 1) and the thermally coupled system with a side stripper (TCDS-SS, Figure 2). Theoretical studies (Tedder and Rudd, 7 Annakou and Mizsey, 8 Dünnebier and Pantelides, 9 among others) have shown that those thermally coupled distillation schemes with side columns are capable of achieving typically 30 % of energy savings compared with the conventional schemes.…”
Section: Introductionmentioning
confidence: 99%
“…tion of these configurations can be found in Agrawal 2000 . Since thermally coupled configurations can often require up to 30 to 40% less heat duty than the conventional direct Ž . and indirect configurations, Annakou and Mizsey 1996 performed a parametric study comparing the performance of the fully-coupled configuration with the double-effect configurations of direct and indirect schemes. They found that double-effect configurations reduced the total heat duty by 10% to 50% when compared to the original direct and indirect schemes.…”
Section: Introductionmentioning
confidence: 99%